FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN JASA KEUANGAN - Sutoyo Sutoyo; Januar Eko Prasetio; Dian Kusumaningrum (University of Merdeka Malang, 2011)
The objective of this research was to analyze what factors influencing dividend payout ratio at the IndonesianStock Exchange (ISE). The method used in this research was the survey method. This research was conductedat the ISE using 82 emitens as the sample based on purposive sampling. The first and second hypothesis wasanalyzed using multiple regression. The result of the first hypothesis analysis showed profitability, liquidity,debt policy, institutional ownership, growth, and firm size simultaneously influential to dividend payoutratio. The second hypothesis analysis showed that only growth influencing dividend payout ratio.